Image-based tree detection for autonomous navigation in orchards - Cadenat, V.; Durand-Petiteville, A.; Billot, D.; Villemazet, A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This paper deals with the autonomous navigation problem through orchards. It highlights the different challenges arising in this particular environment and proposes an adequate framework. This latter relies on a reactive control strategy fed by visual data provided by a set of RGB-D cameras adequately positioned to enlarge the field of view. In this work, we show interest in coupling a deep learning solution for image-based detection with an existing point cloud processing algorithm to improve the overall perception. Experimental results validate the approach.